STRATEGI PEMASARAN BENIH PADI SAWAH (ORYZA SATIVA L.) PADA PB TANI REJO SEED DI YOGYAKARTA - Rahayu, Hanny Fitriana; Listyowati, Esi Asyani; Lutfiadi, Ridwan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
The study aims to identify internal and external environment, to know of the firm, determine alternative and priority marketing strategy. The research method used in this research is a case study method. The analysis used is the analysis of IFE and EFE matrix, IE matrix, SWOT matrix, and QSPM matrix. The results of research based on the IFE matrix have the greatest strength, namely producing quality rice seeds and weaknesses, namely the financial recording system that is not optimal, there are no marketers, promotion that is not optimal, and products cannot be stored for too long. In the EFE matrix, the biggest opportunities are dealers as a source of market information and threats, namely the increasing number of competitors, and the variety rotation system carried out by farmers. Then the IFE and EFE matrices are combined in the IE matrix which shows that PB.Tani Rejo Seed is in cell I. In this position the right strategy is a strategy to grow and develop. Based on the QSPM analysis, there is a strategy with the highest score namely increasing the effective promotion program.